O ensino de química e arte por meio de uma abordagem interdisciplinar com a temática tintas - Reis, Michele Tamara (2018)
In search of integration, articulation and production of new knowledges, in this dissertation, we seek to investigate how an interdisciplinary approach between Chemistry and Art, through the "Inks" theme, can favor the teaching and learning process for high school students. From this perspective, we seek a thematic that provides the study of reality, as well as the contextualization of scientific concepts. This research was developed in a public school of the State network of the city of Santa Maria, with professors of Chemistry and Art, in a third grade class of High School. The research is structured in two phases. The first phase consists in choosing the place, through an online questionnaire applied in different schools and directed to teachers of Chemistry and Art, in order to perceive the interest in developing an interdisciplinary work, besides knowing the school environment. After the definition of the application school, an interview was held with the Chemistry and Art teachers, in order to learn about their conceptions about interdisciplinarity and contextualization, as well as their perspectives regarding the planning and realization of the proposal. The second phase refers to the application of interdisciplinary planning for learners, regarding the theme "Inks". For that, two thematic workshops were elaborated according to the Three Pedagogical Moments, with the use of experimental activities and case study. In this research, the approach is predominantly qualitative, exploratory and descriptive. For data collection, instruments such as questionnaires, interviews, reports and conceptual maps were used and analyzed based on the Discursive Textual Analysis. According to the results obtained in this research, can be observed a gradual evolution of the construction of the knowledge related to the thematic worked, considering the relations established between the concepts organized in the conceptual maps. Therefore, it can be concluded that the theme "Inks" allied to an interdisciplinary approach between Chemistry and Art, provided a more contextualized and integrated teaching process, favoring student learning.